ISMUBA Teacher Strategy in Improving the Quality of ISMUBA Learning After the Covid-19 Era at SMP Muhammadiyah 1 Gamping Sleman - Sutarman; Muhamad Ilham (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The background of the problem in this research is the change in social restriction policy and the transition of learning from face-to-face to distance learning. This change affects the learning process, especially in the Ismuba subject at SMP Muhammadiyah 1 Gamping Sleman, requiring teachers to find new effective strategies to deal with this challenge. In this context, it is important to explore how Ismuba teachers at SMP Muhammadiyah 1 Gamping Sleman face and overcome learning challenges after the Covid-19 era. This research will highlight the learning conditions before and post the pandemic, covering changes that have occurred in learning methods and approaches, as well as their impact on student learning outcomes. The method used is a descriptive qualitative method, some interview data collection, observation and documentation with primary data from three teachers, each of whom teaches ISMUBA subjects. Secondary data was obtained through books, journal articles and internet media, which adapted to this research. The results of this study indicate that learning strategies and conditions play a role in increasing the quality of learning at Muhammadiyah 1 Gamping Sleman Middle School, including: 1) Post-Covid-19 ISMUBA Learning Conditions at Muhammadiyah 1 Gamping Sleman Middle School have changed to face-to-face (offline) this has made learning experience an increase. 2) The ISMUBA learning strategy to increase the quality of ISMUBA learning in the post-covid-19 era at SMP Muhammadiyah 1 Gamping Sleman uses a computer-based e-learning blender strategy and is adapted to student learning styles. 3) The benefits of post-covid-19 ISMUBA teacher learning strategies at SMP Muhammadiyah 1 Gamping Sleman provide benefits such as increased grades achieved, and students' interest and interest in learning has increased.